Evaluating the BizMOOC project Learning to Learn MOOC: The OpenupEd Quality Framework in Action - Rebecca Pitt (International Entrepreneurship Review, 2018)
This paper presents the concept of, and contextualises, Massive Open Online Courses (MOOCs). It subsequently evaluates a MOOC developed to address the European Commission LifeLong Learning (LLL) Key Competency of Learning to Learn during the ERASMUS+ funded BizMOOC project. The paper presents a case study example of the OpenupEd Framework evaluating the Learning to Learn MOOC. This paper presents evidence that an evaluation framework that emphasises the “open” element of MOOC and foregrounds iterative processes to improve the devel-opment of MOOC is vital in the creating genuinely “open” resources. A growing number of businesses, higher education institutions and other stakeholders are engaged, or have an interest, in developing MOOC. This paper adds value by providing a case study example of use of a MOOC evaluation framework and analysing the results.